Intelligent Comparisons II: Operator Inequalities and Approximations - Anastassiou, George A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This compact book focuses on self-adjoint operators' well-known named inequalities and Korovkin approximation theory, both in a Hilbert space environment. It is the first book to study these aspects, and all chapters are self-contained and can be read independently. Further, each chapter includes an extensive list of references for further reading. The book's results are expected to find applications in many areas of pure and applied mathematics. Given its concise format, it is especially suitable for use in related graduate classes and research projects. As such, the book offers a valuable resource for researchers and graduate students alike, as well as a key addition to all science and engineering libraries.
Preface -- Self Adjoint Operator Korovkin type Quantitative Approximation Theory -- Self Adjoint Operator Korovkin and polynomial direct Approximations with rates -- Quantitative Self Adjoint Operator other Direct Approximations -- Fractional Self Adjoint Operator Poincare and Sobolev Inequalities -- Self Adjoint Operator Ostrowski Inequalities -- Integer and Fractional Self Adjoint Operator Opial Inequalities -- Self Adjoint Operator Chebyshev-Gruss Inequalities -- Ultra General Fractional Self Adjoint Operator Representation formulae and Operator Poincare and Sobolev and other basic Inequalities -- Harmonic Self Adjoint Operator Chebyshev-Gruss type Inequalities -- Ultra general Self Adjoint Operator Chebyshev-Gruss type Inequalities -- About a fractional Means inequality.
Keywords: Computational intelligence; Artificial intelligence; Approximation theory; Computational Intelligence; Artificial Intelligence; Approximations and Expansions